Running Together: How Sports Partners Keep You Running - Franken, Rob; Bekhuis, Hidde; Tolsma, Jochem (Frontiers in Sports and Active Living, 2022)
We examined how recreational runners benefit from running with others to maintain a consistent training regimen over time. We used data from the ABS project (“Always Keep Active”). Our sample consisted of more than 800 individuals who had registered to participate in the 2019 edition of the 7K or 15K Seven Hills Run (Nijmegen, The Netherlands) for the first time. Taking advantage of this three-wave, individual-level panel data, we found that increases over time in the number of co-runners (of any ability level) are related to increases in the number of weekly running sessions. The probability of turning up at the Seven Hills Run was positively related to the number of equally or less competent co-runners, and to the number with whom respondents also discussed important matters on a frequent basis. Our recreational athletes differed in the extent to which they expressed social motivations to run. However, among these athletes, the positive impact of sport partners on training frequency did not depend on the importance of social motives. Our study demonstrates that social networks play an important role in maintaining a consistent training habit and in reaching set goals (i.e. participating in a race).